Clinical Factors Influencing Phenotype of HCMV-Specific CD8+ T Cells and HCMV-Induced Interferon-Gamma Production after Allogeneic Stem Cells Transplantation - Inmaculada Gayoso; Sara Cantisán; Carolina Cerrato; Joaquín Sánchez-García; Carmen Martin; Rafael Solana; Antonio Torres-Gomez; Julian Torre-Cisneros (Clinical and Developmental Immunology)
Human cytomegalovirus (HCMV) infection causes significant morbidity and mortality after hematopoietic stem cell transplantation (HSCT). In this work, we characterized the phenotype and interferon-gamma (INF-γ) production of HCMV-specific T cells using QuantiFERON-HCMV assay in 26 patients 6 months after HSCT. We analysed whether these two parameters were associated with clinical variables. Our results showed that the patients receiving stem cells from donors ≥40 years old were 12 times more likely to have HCMV-specific CD8+ T cells with “differentiated phenotype” (CD45RA+CCR7+ ≤6.7% and CD28+ ≤30%) than patients grafted from donors <40 years old (OR=12; P=0.014). In addition, a detectable IFN-γ production in response to HCMV peptides (cutoff 0.2 IU/mL IFN-γ; “reactive” QuantiFERON-HCMV test) was statistically associated with HCMV replication after transplantation (OR=11; P=0.026), recipients ≥40 versus <40 years old (OR=11; P=0.026), and the use of peripheral blood versus bone marrow as stem cell source (OR=17.5; P=0.024). In conclusion, donor age is the only factor significantly associated with the presence of the “differentiated phenotype” in HCMV-specific CD8+ T cells, whereas HCMV replication after transplantation, recipient age, and stem cell source are the factors associated with the production of IFN-γ in response to HCMV epitopes.